Crystal structure of catena-poly[bis(μ2-azido-k2N:N′)-(nitrato-K2N:N′)-bis(1,10-phenanthroline-K2N:N′)samarium(III)], C24H16N11O3Sm - Feng Yu-Quan (Zeitschrift für Kristallographie - New Crystal Structures)
C24H16N11O3Sm, monoclinic, P21/c (no. 14), a = 6.745(6) Å, b = 21.943(19) Å, c = 16.132(14) Å, β = 95.362(13)°, V = 2378(4) Å3, Z = 4, Rgt(F) = 0.0446, wRref(F2) = 0.1162, T = 296 K.